Weather insurance for smallholder tobacco farmers in Malawi - Kapondamgaga, Mwiriha; Fisher, Monica (International Food Policy Research Institute, 2011)
Agriculture is the backbone of Malawi's economy: it accounts for about 34 percent of gross domestic product (GDP), over 90 percent of export earnings, and employment of 85 percent of the population through farming, processing, transportation, and marketing. Given this, and that most farming in Malawi is rain-fed, both Malawi's economy and smallholder farmers are highly vulnerable to variability in rainfall. Since 2005, the World Bank has piloted index-based weather insurance (IBWI) in Malawi to reduce climate-related risks to the agricultural sector. Maize and groundnut farmers were initially targeted, and the pilot programs were expanded in 2007 to cover loans provided to participating smallholder tobacco farmers. In the event of a drought or excess rainfall, the insurance repays part of or the entire loan. The main objective is to reduce loan defaults resulting from weather shocks, increasing farmer access to credit in the future.